2022
DOI: 10.1101/2022.03.15.484510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika virus NS4A hijacks host ANKLE2 to promote viral replication

Abstract: Zika virus (ZIKV) is infamous among flaviviruses for its unique association with congenital birth defects, notably microcephaly. We previously mapped ZIKV-host protein interactions and identified the interaction between ZIKV NS4A and host ANKLE2, which itself has established ties to congenital microcephaly. In fruit flies, NS4A induces microcephaly phenotypes in an ANKLE2-dependent manner. This suggests that NS4A interacts with ANKLE2 to dysregulate cell behavior and contributes to abnormal host neurodevelopme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…This observation, along with the ubiquitous expression of ANKLE2, suggests the potential for a broader post-mitotic function in the ER. Our group has explored this unknown ER function and, recently, showed that it may be coopted for ZIKV replication ( Fishburn et al, 2022a preprint). It is enticing to speculate that the scaffolding function of ANKLE2 could be hijacked by viral proteins, including ZIKV NS4A, to mediate aspects of virus replication in the ER that are otherwise inefficient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation, along with the ubiquitous expression of ANKLE2, suggests the potential for a broader post-mitotic function in the ER. Our group has explored this unknown ER function and, recently, showed that it may be coopted for ZIKV replication ( Fishburn et al, 2022a preprint). It is enticing to speculate that the scaffolding function of ANKLE2 could be hijacked by viral proteins, including ZIKV NS4A, to mediate aspects of virus replication in the ER that are otherwise inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and many other vertebrates ANKLE2 begins with an N-terminal transmembrane (TM) domain that acts as an anchor to the INM and endoplasmic reticulum (ER) membrane. In human cells loss of this TM domain causes ANKLE2 to mislocalize to the cytoplasm ( Elkhatib et al, 2017 ; Fishburn et al, 2022a preprint). Interestingly, invertebrates do not have this TM domain ( Fig.…”
Section: Conservation Of Ankle2 Molecular Architecturementioning
confidence: 99%
See 1 more Smart Citation